SITUATION AND SOLUTIONS TO IMPROVE THE EFFICIENCY OF ODA MANAGEMENT IN VIETNAM - Cai, Nguyễn Thanh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
ODA is an important external resource for poor and developing countries. Over the past time, this capital flow has made great contributions to socio-economic development and poverty reduction in Vietnam. . Attracting and managing the use of ODA is a rather complicated issue. If managed and used effectively, it will be a driving force for socio-economic development and improvement of people’s lives, if If it is not well managed, it will become a debt burden, pushing the country into a state of recession and crisis. The article studies and evaluates the current situation of ODA management and use of Vietnam in recent years, on that basis, proposes some solutions to improve the efficiency of ODA management in the coming time.